Success Factors of Technology Graduates in Selected State Universities and Colleges of the Philippines: Basis for Program Enhancement - Luis Jr. Dulnuan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
This study aimed to determine the success factors of technology program graduates in selected State Universities and Colleges (SUCs) of the Philippines. The independent variables are respondents’ demographics, accreditation status of the technology programs, the morale of respondent, and the practices in the curricular, teaching-learning and assessment, facilities and learning resources, student affairs services, and the organization and management aspects of the technology program while the dependent variables are the graduation rate, graduates’ employment rate, employment status, length of time in acquiring the first job, and monthly income/salary. Findings revealed that the longer the length of service of the faculty, the higher is the graduation rate of the SUCs; State Universities and Colleges with more female faculty generated more graduates than those with more male faculty; the more the SUCs implement the practices in the organization and management of the technology programs, the better the employment rate and higher employment status of their graduates; and State Universities and Colleges with faculty having a shorter length of service generated more graduates with higher employment status and less waiting time before acquiring the first job. Besides, the respondents’ sex and length of service predict the graduation rate while the length of service predicts the graduation status and the length of time of the graduates in acquiring the first job. Moreover, the organization and management significantly predict the employment rate and employment status of graduates.